Enhancing Teachers’ Pedagogical Instruction Through Professional Development Instrument: A Benchmarking Initiative For Faculty Enrichment Plan - et. al., Alfe M. Solina, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The need of classroom observation in assessing teacher’s professional development is regarded as a supportive and developmental process for enhancing the quality of teacher’s pedagogy since it has been widely used to observeand investigate teacher’s instructional practices and provide enhancement of teacher’s classroom instruction based on the collected evidence, constructive feedback, and instructional assessment by the school head, academic chairs and program coordinators. For this study, a researcher-made survey questionnaire approach was carried out and randomly given to group of college instructors. The researchers used the cluster sampling in obtaining the data through classroom observation using the institutionalized professional development tool of a higher education institution. Data gathered were analyzed using the qualitative approach to examine the teacher’s teaching foundations and instructional pedagogical style which main purposes are to identify teacher’s teaching strengths and weaknesses; and to assess where the instructional enhancement is needed. By doing so, it is expected that there will be enhancement in teaching and learning outcomes. The results were examined by making use of Kolb’s Experiential Learning and adopting its four-stage learning cycle which can be used for professional development enhancement.